IDENTIFIKATI PENGARUH FAKTOR PRESTASI KERJA, PROMOSI JABATAN DAN LOYALITAS KERJA TERHADAP KINERJA KARYAWAN - Poniwatie Asmie; Mahsina - (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2018)
This study aims to determine the Effect of Job Performance, Position Promotion and Job Loyalty on the performance of employees of PT Ramayana Lestari Sentosa Tbk in Surabaya. In this digital era and globalization, the development of the retail business world is growing, this brings the level of competition between companies and other companies increasingly tight. This condition has demanded the company to always improve and perfect the core of its business in order to win competition with other companies and maintain the existence of companies in a sustainable manner. This study took Employee respondents at PT Ramayana Lestari Sentosa Tbk in Surabaya with a population of 124 people and 56 respondents were research samples. The data used in this researcher are primary data obtained by distributing questionnaires to all employees. The analysis technique used is multiple linear regression analysis using the F test, t test, and see the dominant effect with a significance level of 5%. The test results proved that the variable Job Performance, Job Promotion and Job Loyalty have a simultaneous and significant effect with the results of multiple linear regression in the F test obtained F count of 166.175 Greater than Ftable 2.78 and the resulting significance value of 0.000 is much smaller than ɑ = (0.05), while the influence is partially significant through t test obtained by tcount for each independent variable, namely Job Performance Variable (X1) of 6.638, Position Promotion (X2) of 4.036, and Work Loyalty (X3) of 3.167 greater than the ttable value of 1.67412, then the independent variable namely Job Performance, Job Promotion and Job Loyalty affect the dependent variable Employee Performance, while the variable work performance has a dominant effect on Employee Performance of PT Ramayana Lestari Sentosa Tbk in Surabaya.